Classification of brain MRI using hyper column technique with convolutional neural network and feature selection method (vol 149, 113274, 2020) - Togacar, Mesut; Comert, Zafer; Ergen, Burhan; Ozyurt, Fatih (Pergamon-Elsevier Science Ltd, 2020)
[Abstract Not Available]